Music in Uganda - Blacking, John (International Library of African Music, 1965)
I visited many parts of Uganda, with the exception of West Nile, and almost everywhere I was struck by the vitality of musical traditions. Even the music played on Western instruments was usually African in idiom. There is, however, an urgent need to co-ordinate research into Ugandan music; to ensure that efficient methods and high standards of scholarship are maintained; to centralize research materials, so that they are readily available to students; and above all to utilize to the full the talents and enthusiasm of the many Ugandans who have already begun to investigate their own music.
Keywords: Ethnomusicology; Research; Music; Musicology; Uganda; African Music